The Network Turn Changing Perspectives in the Humanities - Ahnert, Ruth (Humanities, 2020)
This Element contends that networks are a category of study that cuts across traditional academic barriers, uniting diverse disciplines through a shared understanding of complexity in our world. This title is also available as Open Access on Cambridge Core.